2018
DOI: 10.1002/jcp.26826
|View full text |Cite
|
Sign up to set email alerts
|

Calcium: A novel and efficient inducer of differentiation of adipose‐derived stem cells into neuron‐like cells

Abstract: This study comparatively investigated the effectiveness of calcium and other well-known inducers such as isobutylmethylxanthine (IBMX) and insulin in differentiating human adipose-derived stem cells (ADSCs) into neuronal-like cells. ADSCs were immunophenotyped and differentiated into neuron-like cells with different combinations of calcium, IBMX, and insulin. Calcium mobilization across the membrane was determined. Differentiated cells were characterized by cell cycle profiling, staining of Nissl bodies, detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…To date, a growing body of literature indicates the possibility of a neural differentiation of ASCs. This differentiation is supported by the induction of typical neural marker, evaluated both at protein expression and mRNA levels ( Goudarzi et al, 2018 ), as well as for their functional characteristics ( Jang et al, 2010 ; Guo et al, 2016 ; Ching et al, 2018 ). Moreover, some transcription factors such as Pax6, NeuroD1, Tbr2, and Tbr1, associated to different stages of neurogenesis, were found overexpressed in ASCs after neural induction ( Cardozo et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, a growing body of literature indicates the possibility of a neural differentiation of ASCs. This differentiation is supported by the induction of typical neural marker, evaluated both at protein expression and mRNA levels ( Goudarzi et al, 2018 ), as well as for their functional characteristics ( Jang et al, 2010 ; Guo et al, 2016 ; Ching et al, 2018 ). Moreover, some transcription factors such as Pax6, NeuroD1, Tbr2, and Tbr1, associated to different stages of neurogenesis, were found overexpressed in ASCs after neural induction ( Cardozo et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…CTT JOURNAL | VOLUME 8 | NUMBER 4 | NOVEMBER-DECEMBER 2019 because it has been previously shown that BDNF-expressing hUCB-MSCs have great ability to differentiate into astrocytes and olfactory bulb in mice [24]. Furthermore, adipose tissue, an important source for stem cells, can be considered for differentiation towards a neuronal lineage and olfactory restoration [25][26][27][28]. As shown by Kokai and colleagues, ASCs may differentiate into different cell types, like neural stem cells [25].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…[15][16][17] ADSCs have multipotency, are capable of self-renewing, and can differentiate into types of mesenchymal lineage and transdifferentiate into neurons and glial-like cells. 18,19 Research has shown transdifferentiated ADSCs into neuron-like cells with selectively expressed nestin and neuronal molecules. [18][19][20] Similar results have been reported in functional transdifferentiated ADSCs into motor neuron-like cells (MNLC).…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Research has shown transdifferentiated ADSCs into neuron-like cells with selectively expressed nestin and neuronal molecules. [18][19][20] Similar results have been reported in functional transdifferentiated ADSCs into motor neuron-like cells (MNLC). MNLC showed immunostaining of their processes with ChAT and synaptophysin and their potential for load and unload FM1-43 fluorochrome and synapsed with myotube cells.…”
Section: Introductionmentioning
confidence: 99%